Constructing HEIs Performance - Aditama, Nugroho Prasetyo (PCD Journal, 2025)
This study analyses how higher education institutions (HEIs) performance is constructed within the 2020–2021 Merdeka Belajar-Kampus Merdeka (MBKM) policy, within the context of the strengthening of neoliberal ideology in Indonesian higher education. Using Norman Fairclough's critical discourse analysis approach, this study examines five policy documents and elaborates on them with interviews with five MBKM student participants. NVIVO was used as a tool to facilitate in-depth analysis of the analysed aspects. The results show that the MBKM policy frames HEIs as institutions that support economic growth through discursive representations that emphasise neoliberal logic, such as efficiency, competitiveness, and industrial relevance. Terms such as "independence" and "selling point" are widely used and operated symbolically, obscuring ideological dominance and limiting the autonomy of higher education actors. Indikator Kinerja Utama (IKU) system serves as an instrument for disciplining institutions through the performative construction of HEIs through a series of indicators aligned with neoliberal values. This study emphasise that higher education policy is not neutral but rather part of a social practice shaped by the interests of state actors, industry, and international financial institutions. Therefore, evaluation of HEIs performance needs to include an ideological reading, so that higher education can be returned to a liberating socio-academic role, rather than simply serving market interests.